Microfluidic rectifier based on poly(dimethylsiloxane) membrane and its application to a micropump - Wang, Yao-Nan (AIP Publishing LLC, 2013)
A microfluidic rectifier incorporating an obstructed microchannel and a PDMS membrane is proposed. During forward flow, the membrane deflects in the upward direction; thereby allowing the fluid to pass over the obstacle. Conversely, during reverse flow, the membrane seals against the obstacle, thereby closing the channel and preventing flow. It is shown that the proposed device can operate over a wide pressure range by increasing or decreasing the membrane thickness as required. A microfluidic pump is realized by integrating the rectifier with a simple stepper motor mechanism. The experimental results show that the pump can achieve a vertical left height of more than 2 m. Moreover, it is shown that a maximum flow rate of 6.3 ml/min can be obtained given a membrane thickness of 200 μm and a motor velocity of 80 rpm. In other words, the proposed microfluidic rectifier not only provides an effective means of preventing reverse flow but also permits the realization of a highly efficient microfluidic pump.